CBCT images of anatomic landmarks in maxillofacial region - Mayil, Meltem; Keser, Gaye; Namdar Pekiner, Filiz (My University, 2014)
Conventional radiographic techniques in dental radiology allows only 2D images of 3D structures of head and neck region. CBCT is a recent technology, is also named as dental volumetric tomography, which was developed as an alternative to conventional CT using cone beam-shaped X-ray to provide more rapid acquisition of a data set of entire maxillofacial region. CBCT has remarkable advantages such as shorter exposure time, reduced image distortion due to patient movements, decreased patient dose and multiplanar screening. CBCT also allows the clinicians to localize the anatomic structures of the maxillofacial region and these anatomic structures can be visualized in various planes such as axial, coronal and sagittal planes. In this review we mentioned some anatomic structures of the maxillofacial region by using CBCT imaging.
Keywords: Anatomic landmarks, CBCT, maxillofacial region